John M. Cooper’s Investigation of James Bay Family Hunting Grounds, 1927-1934 - Flannery, Regina; Chambers, M. Elizabeth (Anthropologica, 2022)
Cooper’s 1932 map of the band and hunting territories of the James Bay area has been consulted over the years. In reviewing Cooper’s files, it became apparent that he had intended to revise the map in the light of material he subsequently gathered. Using these data and his working maps, we have made corrections and determined the time periods which the several maps reflect. Discussion of traditional Cree notions about the lands that sustained their livelihood leads us to the conclusion that the term "family hunting grounds" is appropriate and should be retained.